THE PARAPAPIO SPECIES OF STERKFONTEIN, TRANSVAAL, SOUTH AFRICA - Freedman, L.; Stenhouse, N. S. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1972)
The premolar and molar dimensions of the Parapapio specimens hitherto described from the South African lower Pleistocene deposits at Sterkfontein have been re-examined. The relatively minor sexual dimorphism in these teeth (except P3 length) was confirmed. 103 new cercopithecoid specimens from Sterkfontein were tentatively assigned to the 3 previously described Parapapio spp. from that site. The new and old samples of each species were compared and then pooled. Analysis of this new enlarged sample, and also the newly available distribution data of Parapapio from other South African deposits, both tend to support the validity of 3 Parapapio spp., P. jonesi, P. broomi and P. whitei, at Sterkfontein.